Experiences and perceived outcomes of a grocery gift card programme for households at risk of food insecurity - Yun Yun Lee; Stéphanie Caron-Roy; Bobbi Turko; Jane Shearer; David JT Campbell; Charlene Elliott; Donald Barker; Kim D Raine; Sheila Tyminski; Dana Lee Olstad (Cambridge University Press, 2023)
Abstract Objective: This study explored programme recipients' and deliverers' experiences and perceived outcomes of accessing or facilitating a grocery gift card (GGC) programme from I Can for Kids (iCAN), a community-based programme that provides GGC to low-income families with children. Design: This qualitative descriptive study used Freedman et al's framework of nutritious food access to guide data generation and analysis. Semi-structured interviews were conducted between August and November 2020. Data were analysed using directed content analysis with a deductive-inductive approach. Participants: Fifty-four participants were purposively recruited, including thirty-seven programme recipients who accessed iCAN's GGC programme and seventeen programme deliverers who facilitated it. Setting: Calgary, Alberta, Canada. Results: Three themes were generated from the data. First, iCAN's GGC programme promoted a sense of autonomy and dignity among programme recipients as they appreciated receiving financial support, the flexibility and convenience of using GGC, and the freedom to select foods they desired. Recipients perceived these benefits improved their social and emotional well-being. Second, recipients reported that the use of GGC improved their households' dietary patterns and food skills. Third, both participant groups identified programmatic strengths and limitations. Conclusion: Programme recipients reported that iCAN's GGC programme provided them with dignified access to nutritious food and improved their households' finances, dietary patterns, and social and emotional well-being. Increasing the number of GGC provided to households on each occasion, establishing clear and consistent criteria for distributing GGC to recipients, and increasing potential donors' awareness of iCAN's GGC programme may augment the amount of support iCAN could provide to households.